The iterative survey approach in recent trends of teaching the Arabic language (Journal of the College of Basic Education, 2024)
It is no secret to anyone interested in teaching the Arabic language the importance of modern trends in teaching it and increasing the acquisition of its concepts by learners. One of the problems of Arabic is the weakness of learners in the subject of Arabic grammar, which is the backbone of the Arabic language, and mastering its grammar means mastering all of Arabic. The current research aimed to highlight the repetitive inquiry approach as an important approach to the success of teaching the Arabic language in general, especially its grammar. The research addressed, after the research problem, the importance of teaching Arabic grammar, and then the importance of the general inquiry approach. In the second chapter, the inquiry was addressed in the Holy Qur’an and then in the Noble Prophetic Sunnah, and after that how the inquiry process occurs, and its positives And its disadvantages, and finally addressing its various types, as for the third chapter, it dealt with the iterative inquiry approach and how to prepare teaching plans according to its stages, which enables researchers to prepare and formulate integrated educational plans for Arabic grammar rules.